2013
DOI: 10.1186/2193-1801-2-406
|View full text |Cite
|
Sign up to set email alerts
|

New pulse wave measurement method using different hold-down wrist pressures according to individual patient characteristics

Abstract: In traditional Chinese and Korean medicine, doctors first observe a patient’s pulse by gently and strongly pressing their fingers onto the wrist, and then make a diagnosis based on the observed pulse waves. The most common method to implement this diagnostic technique is to mechanically extract the pulse waves by applying a fixed range of pressures for all patients. However, this method does not consider the patients individual characteristics such as age, sex, and skin thickness. In the present study, we prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Alastruey J [16] proposed the R-C circuit model of pulse waves and analyzed the relationship between pressure and flow in the process of pulse wave propagation. Yoo SK et al [17] proposed a gradient pressure measurement method for the differences in biological individuals, obtained the pulse wave under the optimal pulse pressure, and improved the automation and accuracy of pulse wave acquisition. These researchers above focused on the modeling of the time-domain single cycle pulse wave and the analysis of the optimal pulse pressure through the pulse P-S curve, but there is no accurate research model for the formation mechanism of the P-S curve.…”
Section: Introductionmentioning
confidence: 99%
“…Alastruey J [16] proposed the R-C circuit model of pulse waves and analyzed the relationship between pressure and flow in the process of pulse wave propagation. Yoo SK et al [17] proposed a gradient pressure measurement method for the differences in biological individuals, obtained the pulse wave under the optimal pulse pressure, and improved the automation and accuracy of pulse wave acquisition. These researchers above focused on the modeling of the time-domain single cycle pulse wave and the analysis of the optimal pulse pressure through the pulse P-S curve, but there is no accurate research model for the formation mechanism of the P-S curve.…”
Section: Introductionmentioning
confidence: 99%
“…Five different levels of hold -down pressure are measured to characterize the individual subject based on contour of the pulse. BMI of the subject is calculated based on Floating/ Sinking pulse patterns [19]. Comparing the performances of piezoelectric, ultrasonic and piezoresistive pressure sensors with accuracy, sensitivity and positioning, it can be concluded that piezoresistive is superior as it detects weak Kapha pulse amplitude.…”
Section: Piezoelectric Sensorsmentioning
confidence: 99%
“…They considered that temperature would affect the accuracy of tactile sensor and inhomogeneous elasticity at the palpation positions would influence the measured signals in the CP model. Yoo et al [17] proposed a method for pulse wave extraction that incorporates the personal characteristics of the patients. Pulse waves are continuously measured as moving the sensor to press the artery with fixed speed.…”
Section: Introductionmentioning
confidence: 99%